The Development Plan of Mojopahit Marine Tourism: Social-Economy Impact Assessment - Cucu Hayati; Mochamad Ardi Setyawan; Sri Lestari (Airlangga Development Journal, 2022)
This research is urgently needed to be carried out as an initial assessment to forecast the strategic socio-economic issues as the impact toward Mojopahit Maritime Tourism development plan. The analysis is seen from a social context to measure the socio-economic impacts and also the adaptation strategies that will be carried out by the community. An approach for addressing research problems was decided upon: mixed method research. About 101 people who were chosen through clustered random sampling as respondents participated in this study. Distribution of semi-closed-end questionnaires, purposive sampling-based stakeholder interviews, and field observations were used to gather the data. Data analysis was carried out through descriptive analysis and presented in tables and graphs. The validity test of the research was triangulation. Regarding to the Mojopahit Marine Tourism development plan, this study concluded that the community has sufficient knowledge in measuring the socio-economic impacts of Mojopahit Marine Tourism development plan, including unemployment issue, congestion issue, bio degradation issue, land/building ownership changing, and economic activities changing. Although Mojopahit Marine Tourism will be established in the next year, policy makers have made physical, social, and economic preparations to welcome this development plan through an agent called Tourism Awareness Group (Pokdarwis), socialization programs through digital platforms, and collaborative preparation among departments, city government, district government, as well as village government. It is hoped that the growth of tourism will benefit all Mojokerto local people.